Effect of preparation process on purity of tricalcium aluminate - Simona Ravaszová; Karel Dvořák; Andrea Jančíková (Acta Polytechnica CTU Proceedings, 2024)
In the realm of cement production, traditional fuels are steadily giving way to alternative sources. While this shift yields economic and ecological advantages, it introduces notable technological challenges. Specifically, there is an escalation in certain chemical elements, leading to variability in the mineralogical composition. This variability is subsequently manifested in the characteristics of Portland clinker. It becomes imperative, therefore, to synthesize pure clinker minerals. This synthesis is essential for both understanding their behavior in industrially manufactured cement and creating analytical standards for mineral identification through XRD. The primary focus of the research is on the production of pure tricalcium aluminate, a key clinker mineral, within laboratory conditions. A direct laboratory methodology involving solid-phase synthesis is used. The investigation meticulously tracks the impact of homogenizing the raw material mixture on the resultant mineral’s purity. To achieve this, a high-speed Pulverisette 6 planetary mill is utilized along with two types of grinding bodies. A corundum grinding capsule with corundum grinding bodies is employed to prevent contamination by foreign ions. Simultaneously, a highly efficient steel grinding capsule with steel grinding bodies is utilized. The raw material mixture is then subjected to sintering at six different temperatures ranging from 1 200 to 1 450 °C, and the purity of the produced mineral is quantified using Rietveld analysis. Laser granulometry results indicate a strikingly similar comminution of the raw material in both grinding cases. Iron contamination, as revealed by XRF analysis, is minimal, accounting for only 0.21 %. The purity of 97.6% C3A, is achieved at 1 450 °C using a steel grinding capsule, with 2.4% unreacted lime Conversely, when using a corundum capsule, a purity of 93.6 % is achieved, accompanied by residues of 2.2 % mayenite and 3.8 % lime. This discrepancy may be attributed to an insufficient degree of raw material comminution in the corundum capsule. Intriguingly, a slight iron contamination during the grinding of the raw material mixture exerts a positive influence on purity. In this case, iron acts as a flux, fostering a more favorable reaction of the mineral mayenite. This multifaceted exploration enhances our understanding of clinker mineral synthesis, offering insights into optimizing purity based on grinding methods, sintering temperatures, and the impact of minor contaminants.